Protein-olive oil-in-water nanoemulsions as encapsulation materials for curcumin acting as anticancer agent towards MDA-MB-231 cells - Pankaj Bharmoria (Nature Portfolio, 2021)
Abstract The sustainable cellular delivery of the pleiotropic drug curcumin encounters drawbacks related to its fast autoxidation at the physiological pH, cytotoxicity of delivery vehicles and poor cellular uptake. A biomaterial compatible with curcumin and with the appropriate structure to allow the correct curcumin encapsulation considering its poor solubility in water, while maintaining its stability for a safe release was developed. In this work, the biomaterial developed started by the preparation of an oil-in-water nanoemulsion using with a cytocompatible copolymer (Pluronic F 127) coated with a positively charged protein (gelatin), designed as G-Cur-NE, to mitigate the cytotoxicity issue of curcumin. These G-Cur-NE showed excellent capacity to stabilize curcumin, to increase its bio-accessibility, while allowing to arrest its autoxidation during its successful application as an anticancer agent proved by the disintegration of MDA-MB-231 breast cancer cells as a proof of concept.